Capitalization Chronicles: Unraveling the Impact on Bank Profitability - Ririen Setiati Riyanti (Jurnal Akuntansi dan Keuangan, 2024)
This study seeks to investigate the influence of capitalization on the profitability of banks, focusing on financial data of 34 Indonesian commercial public banks over the period of 2013-2022. The researcher evaluates the capital ratio, a critical measure of financial stability, for its impact on key profitability metrics such as Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Pre-Provision Profitability Ratio (PPR).  By utilizing the Fixed Effect Model (FEM), the results of this study show mixed effects of capital ratio on profitability across profit measures. Further, the finding shows an inverted U-shaped impact of capital ratio on bank profit when ROA is used. This suggests that a higher capital ratio increases a bank’s ability to generate profits on its assets up only to a critical point. A further increase in the capital ratio beyond this point tends to adversely affect profitability.